Od „správců věrné ruky“ ke „komisařům“. K etablování tzv. komisařů pro uzavřené české vysoké školy, 1939–1940 - Michal V. Šimůnek; Miloš Hořejš (Acta Universitatis Carolinae: Historia Universitatis Carolinae Pragensis)
The chief aim of the forcible closing of Czech universities on 17 November 1939 was to stop university education and persecute students but this step had also created a number of political, technical, and last but not least also administrative problems and challenges. After Adolf Hitler decided in early December 1939 that some institutes would be allowed to renew their activities in a modified and closely supervised form, what turned out to be especially important was the administrative form which the German authorities would opt for. After about onemonth-long deliberation, it was decided that so-called commissars (Kommissare) would play a key role in this process. Their functioning, which gradually acquired concrete forms in the course of 1940, was approached rather innovatively, especially in terms of exploitation of this key part of Czech scientific infrastructure.